PENGARUH NET PROFIT MARGIN DAN RETURN ON EQUITY TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2020-2023 - Amelia, Sofiyatul; Wahyuni, Ika; Subaida, Ida (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Amid increasingly intense global competition, the effective use of data has become essential for companies to remain competitive. Therefore, variables such as net profit margin, return on equity, and firm size are crucial for gaining deeper insights into firm value and its impact on company performance. This study focuses on food and beverage companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The objective of this research is to analyze and identify the influence of net profit margin and return on equity on firm value, with firm size acting as a moderating variable. A quantitative method was employed, utilizing secondary data obtained from annual reports available on the official IDX website (www.idx.co.id). The sampling technique used was purposive sampling, resulting in a total of eight companies selected as the sample. Data analysis included descriptive statistics, classical assumption tests (normality and multicollinearity), the coefficient of determination test, and structural equation modeling. Hypothesis testing using Smart PLS 3.0 software revealed that the net profit margin has a negative but non-significant effect on firm value. At the same time, the return on equity has a positive but also non-significant effect. Furthermore, firm size does not significantly moderate the relationship between either net profit margin or return on equity and firm value.